Sistem Monitoring Charger Baterai VRLA Menggunakan Switch Mode Power Supply Berbasis Internet Of Things - Muhammad Alfarizqi; Widjonarko; Triwahju Hardianto (FORTEI Regional VII Jawa Timur, 2025)
The VRLA battery charging process using a Switch Mode Power Supply (SMPS) in this test plays a very active role in maintaining battery reliability. In the SMPS there are CC and CV that regulate a stable current at 1.8 Amperes and a voltage at 14.1 volts. Charging is integrated with the IoT system by utilizing Arduino mega communication with esp32 which is connected to the application for monitoring and controlling the cut-off relay. The esp32 Rx is connected to the Arduino mega tx and the esp32 tx is connected to the Arduino rx which makes both communicate two-way. Charging an 18Ah battery takes place for 2 hours and 16 minutes with an initial voltage of 13.44 volts, a stable current of 1.787 amperes, and a duty cycle of 21.24% in CC mode, while CV mode starts at a voltage of 14.1 volts with a current slowly decreasing to 0.3 amperes and approaching the automatic or manual cut-off relay switching mode to continue charging the 2nd battery, namely 5Ah. The 5Ah battery charging process is faster due to its smaller capacity and higher initial voltage compared to 18Ah, so the charging time is only 45 minutes. In this study, the cut-off relay switching and monitoring system works very well with a small error of 0.55% and a fast switching time of 1.3 seconds.